Analisa Faktor-Faktor Yang Mempengaruhi Gula Darah Pada Penderita Diabetes Meilitus Tipe 2 Di RSUD Cempaka Putih - Tri Atmoko; Solehudin Solehudin; Lanasari Lanasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diabetes mellitus (DM) is a serious chronic disease caused by the pancreas that does not produce enough insulin. His high blood sugar levels marked the influence of factors that occur. Therefore, the patient must understand what influences make his blood sugar levels higher. This study aims to analyze the factors that affect blood sugar. The research method used correlational analysis with sectional design and total sampling techniques.